Expense for Clinical Documentation of Inpatients: Extent and Hierarchal Differences for the Example of a Gynaecological Department in Switzerland - Thanner, M.; Drack, G.; Hornung, R. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: The majority of physicians consider administrative tasks to be a burden. The present questionnaire is intended to clarify the expense of time for documentation tasks in the treatment of inpatients in a gynaecological department of a Swiss hospital and to what extent differences occur between senior physicians and junior physicians. Materials and Methods: For three weeks physicians in the gynaecological department of a central Swiss hospital documented minute for minute predefined tasks during their duty periods. A questionnaire in tabular form served as survey instrument for this working time analysis. The minute for minute details for the individual participants were summed for each clinical task listed in the questionnaire in order to subsequently calculate the amounts of time spent for the respective task categories and to subject them to a subgroup analysis. Results: The participation rate of the physicians amounted to 87 %. 287 questionnaires were included in the evaluation. According to the responses, 25 % of the clinical working time for inpatients was used for documentation of clinical tasks. The subgroup analysis revealed a higher proportion for assistant physicians (30 %) than for senior physicians (18 %). Discussion: The present working time analysis reveals an unfavourable ratio between surgical and administrative tasks between junior and senior physicians. In addition there is a danger that the true burden for junior physicians is underestimated by their superiors due to hierarchal differences.
Keywords: documentation; administration; time study; hospital